Papel da apoptose no infiltrado inflamatório do líquen plano bucal - Juliana Massote Caldeira Brant (2012)
The Oral Lichen Planus (OLP) is a chronic inflammatory autoimmune disease whose most common clinical forms are the reticular and erosive types. The persistence of the subepithelial inflammatory infiltrate is important in the pathogenesis of OLP, but the mechanisms involved in this process still have to be investigated. The deficiency of apoptosis may contribute to persistence of the infiltrate, which is comprised predominantly of subepithelial CD4+ and CD8+ T lymphocytes. The target of CD8+ T lymphocytes are the keratinocytes in OLP. The objective of this study was to evaluate the blockage of apoptosis in subepithelial lymphocytes, the involved pathway and quantify CD8+ T lymphocytes in reticular and erosive types of OLP. Fifteen samples of each reticular and erosive types of OLP and 15 samples of mucosa with inflammatory fibrous hyperplasia (control group) were selected. Proteins Bax, Bcl2, Caspase-3 and -8 and CD8 were quantified by Immunohistochemistry. Intense labeling to CD8 (37.03%, erosive and 32.02%, reticular), and to Bcl2 (53.61%, erosive and 32.05%, reticular) occurred in samples of OLP awhile in the control group labeling were scarce (27.37% and 17.74%, respectively). There was no difference in immunoexpression of CD8 between the reticular and erosive types of OLP (p>0.05). Bcl2 labeling was more intense in erosive type than in reticular type (p<0.05). On the other hand, immunoexpression of Caspase-8 (0.44%, erosive and 0.41%, reticular) and Caspase-3 (0.87%, erosive and 0.89%, reticular) were poor in inflammatory infiltrates of OLP and were intense in the control group (31.65%, Caspase-8 and 34.95%, Caspase-3). Bax antibody did not result any labeling in OLP and in thecontrol groups. Low expression of Caspase-8 and Caspase-3 in inflammatory infiltrates of OLP indicate that the extrinsic pathway of apoptosis is not active in those lesions. The low expression of Bax and Caspase-3 and the high expression of Bcl2 in inflammatory infiltrates of OLP indicate that the intrinsic pathway is active, but may be blocked by anti-apoptotic proteins. In addition, the more intense expression of Bcl2 in inflammatory infiltrates in erosive than in reticular types demonstrates a greater tendency to evasion of apoptosis and persistence of inflammation in erosive type.